IL-1B rs2853550 polymorphism contributes to esophageal cancer susceptibility in Chinese Han population of Northwest China - Ruimin Zhao; Xin Chen; Wanli Ren; Hao Dai; Huajing Li; Honghui Li; Ai Jia; Yue Wu; Peng Han; Yuan Shao (BMC, 2020)
Abstract Background Esophageal cancer (EC) is one of the most common human cancers, with a particularly aggressive behavior and increased incidence worldwide. The aim of this study was to assess the associations of single-nucleotide polymorphisms (SNPs) in IL-1B with the risk of EC in a northwest Chinese Han population. Methods In order to evaluate the correlations between IL-1B polymorphisms and EC risk, an Agena MassARRAY platform was used to determine the genotype of the candidate SNPs among 384 EC patients and 499 controls. The associations between IL-1B variants and EC risk were examined using logistic regression analysis with adjustment for gender and age. Haplotype construction and analysis were performed to detect the potential associations between haplotypes within IL-1B and EC susceptibility. Additionally, bioinformatics databases were used for gene expression analysis and SNP functional prediction. Results A significant relationship was found between IL-1B rs2853550 and an increased risk of EC in the allele model [odds ratio (OR) = 1.38, 95% confidence interval (95% CI): 1.01-1.89, p = 0.041), the codominant model (A/G, OR = 1.63, 95% CI: 1.10-2.42, p = 0.011), and the dominant model (OR = 1.49, 95% CI: 1.02-2.18, p = 0.041). Functional analysis revealed the potential effects of rs2853550, which further reinforced its influence on EC susceptibility. However, there were no statistically significant differences for other SNPs or haplotypes between EC cases and healthy controls. Expression analysis conducted with dataset indicated that the expression level of IL-1B was higher in EC cases than that in normal samples. Conclusions This study demonstrated that rs2853550 in IL-1B might increase EC susceptibility in the Chinese Han population of Northwest China.